Development of Pop-Up Book Learning Media Assisted by QR Code to Increase Student Learning Motivation in Science Material - Yanuardianto, Elga; Ilyas, Muhammad; Wafa, Muhamad Ali (Fakultas Tarbiyah dan Ilmu Keguruan Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2023)
The use of appropriate learning media and in accordance with the needs of students, will create an active and fun learning atmosphere for students. This research and development produces learning media in the form of Pop up books assisted by Qr codes can be an effort to create an active learning atmosphere and can increase student learning motivation in the classroom. The purpose of this study was to analyze the ADDIE model in the development of Science Learning media With Pop Up Book Media assisted by Qr Code on the material of plant parts. The type of research used is research and development model with ADDIE model implemented until the implementation step. The results of this study show that; 1) the development Model of Pop-up Book Learning Media assisted by Qr Code in increasing student learning motivation, namely the results of Pop-up Book in Qr Code there is a video along with an explanation of the material. Developed products meet the components as teaching materials in learning. 2) P and feasibility test of the results of the development of Pop-up Book Learning Media assisted by Qr Code in increasing student learning motivation is carried out through media experts, material experts.